Dual-phase titanate/anatase with nitrogen doping for enhanced degradation of organic dye under visible light - Kanhere, Pushkar D. (2012)
Synergy at work! A dual-phase photocatalyst comprising anatase and protonated titanate, synthesized by a low temperature one-pot process, synergistically adsorbs and degrades methylene blue dye under visible light. The two phases (see figure) work harmoniously to give accelerated breakdown of the organic dye.